2017
DOI: 10.1109/jsac.2017.2699360
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Beam Alignment: Large Deviations Analysis and Design Insights

Abstract: Abstract-In millimeter wave cellular communication, fast and reliable beam alignment via beam training is crucial to harvest sufficient beamforming gain for the subsequent data transmission. In this paper, we establish fundamental limits in beam-alignment performance under both the exhaustive search and the hierarchical search that adopts multi-resolution beamforming codebooks, accounting for time-domain training overhead. Specifically, we derive lower and upper bounds on the probability of misalignment for an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 31 publications
1
102
0
Order By: Relevance
“…Based on measurements in , the directional path loss was modeled in terms of the number of multipath components by considering the both coherent and non‐coherent received power combining . Theoretical analyses of beam misalignment with idealized antenna patterns were conducted in . For a backhaul link, beam self‐alignment with combined transmit–receive searching for proper beamforming patterns for multilevel codebook sets was investigated in .…”
Section: Introductionmentioning
confidence: 99%
“…Based on measurements in , the directional path loss was modeled in terms of the number of multipath components by considering the both coherent and non‐coherent received power combining . Theoretical analyses of beam misalignment with idealized antenna patterns were conducted in . For a backhaul link, beam self‐alignment with combined transmit–receive searching for proper beamforming patterns for multilevel codebook sets was investigated in .…”
Section: Introductionmentioning
confidence: 99%
“…Proof: See Appendix D. Specifically, in [12], we have proved that exhaustive search asymptotically outperforms hierarchical search 2 in the sense that its misalignment probability has a larger decay rate (with respect to the training energy budget) quantified by…”
Section: B Asymptotic Performance Analysis and Further Insightsmentioning
confidence: 87%
“…BEAM CODEBOOK Similar to [9], [12], for tractability, we focus the analysis on a rank-one channel model that captures well the dominant path in a LOS environment. More general models will be numerically investigated in Section V, and it will be shown that the insights generated from the analysis here continue to apply therein.…”
Section: Performance Analysis Under Single-path Channel Model Andmentioning
confidence: 99%
“…In the current special issue of IEEE JSAC, the signal processing schemes on mmWave MIMO are investigated in [174]- [189]. Specifically, in [174], a receive antenna selection (RAS)-aid spatial modulation scheme is proposed to reduce the RF complexity, and an iterative algorithm is proposed to search the antenna index with low complexity.…”
Section: F Recent Progressmentioning
confidence: 99%